In the name of the father: Verwoerd, W (1997) My winds of change. Randburg: Ravan Press. ISBN 0-86975-513-7. 176 pages. (Verwoerd, W (1996) Viva Verwoerd? Cape Town: Human & Rousseau - Afrikaans edition). - Coetzee, Carli (PINS-Psychology in Society, 2026)
In the autobiography by Wilhelm Verwoerd, grandson of the architect of apartheid, issues of names and lineages are, not surprisingly, dominant. The Afrikaans edition has the title Viva Verwoerd?, the question mark calling into question the meanings of the name, and the legacy handed down from his father and grandfather.